2008
DOI: 10.1108/09513570810872905
|View full text |Cite
|
Sign up to set email alerts
|

Towards the feminization of accounting practice

Abstract: Purpose -The purpose of this paper is to open up the Anglo-centred argument in gender and accounting by exploring the relationship of women and accounting in a different social and cultural context. Design/methodology/approach -The paper draws on in-depth ethnographical studies to explore the real-life experiences of 66 Japanese women (9 percent of all women CPAs) who have entered the accounting profession from a range of backgrounds and generations. Findings -The paper finds that some women accounting profess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
70
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 101 publications
(76 citation statements)
references
References 47 publications
(81 reference statements)
4
70
0
2
Order By: Relevance
“…The consideration of gender in the accounting literature has mostly been developed in Anglo‐Saxon studies (Hopwood, ; Ciancanelli et al , ; Collins, ; Anderson et al , ; Dennis et al , ; Hull & Umansky, ; Almer et al , ; Anderson‐Gough et al , ; Keller et al , ; Gold et al , ). In this context, along with the work of Komori (, p. 507), our study helps to ‘open up the Anglo‐centred argument in gender and accounting by exploring the relationship of women and accounting in a different social and cultural context’.…”
Section: Contributions Limitations and Perspectivesmentioning
confidence: 89%
See 3 more Smart Citations
“…The consideration of gender in the accounting literature has mostly been developed in Anglo‐Saxon studies (Hopwood, ; Ciancanelli et al , ; Collins, ; Anderson et al , ; Dennis et al , ; Hull & Umansky, ; Almer et al , ; Anderson‐Gough et al , ; Keller et al , ; Gold et al , ). In this context, along with the work of Komori (, p. 507), our study helps to ‘open up the Anglo‐centred argument in gender and accounting by exploring the relationship of women and accounting in a different social and cultural context’.…”
Section: Contributions Limitations and Perspectivesmentioning
confidence: 89%
“…This work therefore contributes to extending the field of gender studies in the accounting domain. In addition, performing this study in a French context enables us to widen the geographic scope of accounting studies on gender (Annisette, ; Komori, ). The consideration of gender in the accounting literature has primarily been developed in Anglo‐Saxon studies (Hopwood, ; Ciancanelli et al , ; Collins, ; Anderson, Johnson & Reckers, ; Dennis, Engle & Stephens, ; Hull & Umansky, ; Almer, Hopper & Kaplan, ; Anderson‐Gough, Grey & Robson, ; Keller, Smith & Smith, ; Gold, Hunter & Gomaa, ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The career advancement of part-time workers depends upon the extent of their ambition to advance (Benschop, van den Brink, Doorewaard, & Leenders, 2013). Komori (2008) compared gender and accounting in Japan with that of Anglo-Saxon countries, and found that problems faced by Japanese women in accounting are similar to that of women in Anglo-Saxon countries. However, Japan is an interdependent society, and, therefore, they use different ways to mitigate gender discrimination.…”
Section: Organizational Structure and Gendermentioning
confidence: 99%